2010
DOI: 10.1104/pp.110.165332
|View full text |Cite
|
Sign up to set email alerts
|

Unique Thylakoid Membrane Architecture of a Unicellular N2-Fixing Cyanobacterium Revealed by Electron Tomography    

Abstract: Cyanobacteria, descendants of the endosymbiont that gave rise to modern-day chloroplasts, are vital contributors to global biological energy conversion processes. A thorough understanding of the physiology of cyanobacteria requires detailed knowledge of these organisms at the level of cellular architecture and organization. In these prokaryotes, the large membrane protein complexes of the photosynthetic and respiratory electron transport chains function in the intracellular thylakoid membranes. Like plants, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 31 publications
5
49
1
Order By: Relevance
“…Cells were prepared for electron microscopy essentially as described (Liberton et al, 2011). Culture aliquots (approximately 15 mL) were centrifuged, and the pellet was resuspended in a small volume, transferred to planchettes with 100-to 200-mm-deep wells, and frozen in a Baltec High Pressure Freezer (Bal-Tec).…”
Section: Electron Microscopymentioning
confidence: 99%
“…Cells were prepared for electron microscopy essentially as described (Liberton et al, 2011). Culture aliquots (approximately 15 mL) were centrifuged, and the pellet was resuspended in a small volume, transferred to planchettes with 100-to 200-mm-deep wells, and frozen in a Baltec High Pressure Freezer (Bal-Tec).…”
Section: Electron Microscopymentioning
confidence: 99%
“…PCC 6803 convert light to cellular energy, an ability that makes these organisms of particular interest in renewable energy studies. Cyanobacteria typically have a Gram-negative-type cell envelope consisting of a plasma membrane (PM) 1 , peptidoglycan layer, and outer membrane. These microbes also have an internal thylakoid membrane (TM) system where the protein complexes of the photosynthetic and respiratory electron transfer chains function.…”
mentioning
confidence: 99%
“…This architecture is similar to what we reported in our examination of cells from the L10 time point. 13 In tomographic slice images, the thylakoid membranes appeared sheet-like and the areas where the membranes branched could be clearly observed (Fig. 1A-E).…”
Section: Handedness Of the Thylakoid Arrangement In Cyanothece 51142mentioning
confidence: 97%
“…In fact, only within the past few years has work using tomographic data shown that thylakoid membranes are connected by channels or bridging membranes in some cyanobacterial strains. 11,12 Our recent work 13 examining the thylakoid membrane system in Cyanothece 51142 depicted, for the first time, a membrane system in a cyanobacterium with strong similarities to that in plants: a highly interconnected network composed by branching is very dense, with a larger number of membrane layers compared to what has been observed in other cyanobacteria. 13 It is possible that helical organization originated as a primarily left-handed architecture, followed by the development of grana and the attendant right-handedness of the grana-stroma architecture at a later time.…”
Section: Handedness Of the Thylakoid Arrangement In Cyanothece 51142mentioning
confidence: 99%
See 1 more Smart Citation